Vitamin K-dependent carboxylation and vitamin K metabolism in liver. Effects of warfarin. - Wallin, R (1985)
The systems involved in vitamin K-dependent carboxylation and vitamin K metabolism have been extensively studied in rat liver. To determine how clinically applicable this information is, similar in vitro studies were completed using human liver. One major difference exists in the pathways that provide reduced vitamin K1 cofactor for the carboxylation reaction. The coumarin-sensitive DT-diaphorase (EC.1.6.99.2) in human liver appears to play a relatively minor role in the dehydrogenase pathway. However, similar to rat liver, the human liver contains a warfarin-insensitive enzyme in this dehydrogenase pathway. The data suggest that this enzyme is responsible for the antidotic effect of vitamin K1 in cases of coumarin intoxication. Human vitamin K epoxide reductase, which constitutes the other pathway for vitamin K1 reduction, has kinetic and enzymological characteristics that are very similar to the rat enzyme. This enzyme exhibited similar activity in rat and human microsomes. Initial velocities for vitamin K1 epoxide reduction in rat and human microsomes were 20 and 32 pmol/mg X min, respectively. The human enzyme is highly sensitive to warfarin inhibition. The mechanism for this inhibition appears to be similar to what has been proposed for the rat enzyme. Also, a vitamin K-dependent carboxylation system is described that allows both pathways to support the carboxylation reaction with reduced vitamin K1 cofactor. The effect of warfarin on this in vitro system is consistent with the current model for the mechanism of action of coumarin anticoagulant drugs in the rat.